Molecular characterization of accessions of crabgrass (Digitaria nuda) and response to ametryn - DOI: 10.4025/actasciagron.v32i2.3841 - Vieira, Viviane Cristina (2010)
Digitaria species are sugar cane crop weeds in Brazil and are being controlled with herbicides, although there are some reports of control failure, notably to the triazine group. Molecular techniques are recommended to analyze the genetic variability in weeds. RAPD (Random Amplified Polymorphic DNA), PCR-RFLP (Polymerase Chain Reaction – Restriction Fragment Length Polymorphism) and, in combination with sequencing, allow the localization of resistance genes, as well as possible mutations related to the onset of resistant individuals in some species. Thus, the objective of this work was to characterize ten accessions of Digitaria spp. by RAPD and PCR-RFLP markers, to sequence a conserved region of the psb A gene and evaluate the accessions response to ametryn. As showed by molecular analysis there was high genetic similarity among the accessions, all of them presented similar genetics profiles and were susceptible to ametryn.